3D Telomere Structure Analysis to Detect Genomic Instability and Cytogenetic Evolution in Myelodysplastic Syndromes - Aline Rangel-Pozzo; Daiane Corrêa de Souza; Ana Teresa Schmid-Braz; Ana Paula de Azambuja; Thais Ferraz-Aguiar; Tamara Borgonovo; Sabine Mai (Cells, 2019)
The disease course of myelodysplastic syndromes (MDS) features chromosome instability and clonal evolution, leading to the sequential acquisition of novel cytogenetic aberrations and the accumulation of these abnormalities in the bone marrow. Although clonal cytogenetic abnormalities can be detected by conventional cytogenetics in 50% of patients with MDS, such distinguishing patterns are lacking in the other 50%. Despite the increase in the prognostic value of some biomarkers, none of them is specific and able to discriminate between stable and unstable patients that subsequently progress to acute myeloid leukemia. This pilot study aimed to investigate the potential use of the 3D telomere profiling to detect genomic instability in MDS patients with or without clonal cytogenetic evolution. The comparison between different time points in patients with cytogenetic changes showed that in the CD34+ MDS cells, there was a significant decrease in the total number of telomeric signals, the average intensity of signals and the total intensity of telomeres. By contrast, the number of aggregates increased during cytogenetic evolution (p < 0.001). This pattern was observed only for MDS patients with cytogenetic evolution but was absent in patients without cytogenetic changes. In conclusion, we demonstrated that the 3D nuclear telomere organization was significantly altered during the MDS disease course, and may have contributed to cytogenetic clonal evolution.